Assessment of High-temperature Component Containing Multiple Flaws. (November 2020) - Si, Jun; Ren, Facai; Ren, Bin; Tang, Xiaoying
Abstract: Multiple flaws are often found in many high-temperature components. The interaction of multiple flaws may significantly affects service life of high-temperature components. Flaws re-characterization rules for multiple flaws have been proposed in ASME and BS7910. However, most rules are formulated according to the elastic fracture parameter. Due to the different failure mechanism among linear-elastic stress conditions, elastic-plastic conditions and high-temperature creep conditions, the interacting behavior of components containing multiple flaws is also different. Therefore, it is the important to investigate the interacting behavior of multiple flaws under the high-temperature creep conditions. In the current work, the high-temperature creep fracture parameter is calculated for plate containing multiple flaws by using the finite element analysis (FEA) under the tensile load. Based on these analyses, the new re-characterization rules are proposed to exclude the non-conservativeness caused by the current re-characterization rules in high-temperature creep conditions for heat-resistant steel. The coalescence rule for collinear cracks is S ≤2.5 a, and the parallel cracks can be treated as collinear cracks for all distance S when the equation h ≥ a is satisfied.